IMPLEMENTASI PERATURAN DAERAH NOMOR 17 TAHUN 2015 TENTANG PENANGGULANGAN MASALAH GELANDANGAN DAN PENGEMIS (GEPENG) (STUDY KASUS DI KECAMATAN AMUNTAI TENGAH KABUPATEN HULU SUNGAI UTARA) - Siti Raudah (Jurnal PubBis, 2019)
Implementation of Regional Regulation Number 17 Year 2015 on Efforts to Overcome Problems of Villagers and Beggars (Case Study in Amuntai Tengah Sub-District Hulu Sungai Utara). The increasing number of homeless and beggars in Amuntai City of Hulu Sungai Utara Regency is 119 people, and the addition is due to other areas coming from 23 people, that is from Banjarbaru, Tenggarong, Banjarmasin, Malang and Barabai so that the total is all 142. The number will disturb the name of the smooth development of the region, for example, the problem of security and public order. The purpose of this research is to identify and analyze the implementation of Local Regulation and to analyze the obstacles in implementing Local Regulation Number 17 year 2015 on Efforts to Overcome Problems of Villagers and Beggars in Amuntai City of Hulu Sungai Utara Regency. The research method is descriptive qualitative, type and source of data that is primary data through observation, interview while secondary data through existing data at Social Service and Satpol PP of Hulu Sungai Utara Regency, technique used in sampling that is Snow-Ball sampling technique snowball sampling). From the results of the research shows that In the implementation of Regional Regulation Number 17 year 2015 on the Prevention of Problems of Beggars and Beggars in Amuntai City of Hulu Sungai Utara Regency, still not fully implemented, it is seen that shelter houses for street children and homeless shelters are not built when this is an effort in tackling the widespread problem of the Homeless and the Beggar. However, persuasive guidance has been done by the Social Service and Satpol PP at the time of capturing or patrolling for controlling the street children. The suggestions provided for the input materials include Building Homes for the shelter of homeless and beggars who have no home, and can provide guidance on skills training to be more independent, Must have the attention and support from the Regent of Hulu Sungai Utara related problems the provision of budget funds in terms of supporting efforts to overcome the problems of homeless and beggars in Amuntai City so that security and order be better and achievement of regional development goals. Keywords: implementation; countermeasures; vagrant and beggar